Validation of a Tool to Evaluate Drug Prevention Programs Among Students - Galvão, Patrícia Paiva de O.; Valente, Juliana Y.; Millon, Jacqueline N.; Melo, Márcia H. S.; Caetano, Sheila C.; Cogo-Moreira, Hugo; Mari, Jair J.; Sanchez, Zila M. (Frontiers in Psychology, 2021)
Background: School-based prevention programs have been implemented worldwide with the intention of reducing or delaying the onset of alcohol and drug use among adolescents. However, their effects need to be evaluated, being essential to use validated and reliable questionnaires for this purpose. This study aimed to verify the semantic validity and reliability of an instrument developed to evaluate the results of a government drug prevention program for schoolchildren called #Tamojunto2.0. Methods: This is a mixed methods study with quantitative (test-retest and non-response evaluation) and qualitative analyses (focus group and field cards). The self-administered questionnaires were used for a sample of 262 eighth-grade students (elementary school II) in 11 classes of four public schools in the city of São Paulo. Results: The level of agreement was substantial (Kappa 0.60 to 0.79) or almost perfect (Kappa > 0.8) for almost all questions about the use of marijuana, alcohol, cigarettes, cocaine, crack, and binge drinking. The focus groups and field cards provided high-quality information that helped the researchers identify the main difficulties in applying and understanding the questions. Conclusion: The questionnaire showed high reliability and understanding by adolescents. After the necessary changes, identified in this study, the questionnaire will be suitable to evaluate the results of the #Tamojunto2.0 program in a randomized controlled trial.